The Impact of Signs and Symptoms on the Quality of Life in Patients with Rheumatoid Arthritis Referred to the Hospitals of Tehran University of Medical Sciences in Year 2005 - Z. Monjamed; F. Razavian (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2007)
Background and objectivesRheumatoid arthritis is one of the most common chronic diseases of unknown cause leading to significant disabilities especially in the adult patients. The physical signs and symptoms of this chronic disease can considerably affect the patients’ quality of life. MethodsIn this relationship survey, 190 randomly selected patients with rheumatoid arthritis. The data were collected through self-reports, interview and observation by questionnaire, and using the pain and fatigue severity scales, which consisted of eight items. Statistical analyses using descriptive and inferential methods were performed by SPSS software (version 11.5).ResultsThe results showed that the quality of life was high to moderate in half of the subjects (%50) and low in the other 50%. The status of physical dimensions, socio-economic, mental, sleep and rest, and general health was high to moderate in 50% and low in the other 50% of patients. The intensities of pain, fatigue, anxiety, and depression were severe in most cases, but the disability in mobility was mild. There was a significant relationship between intensity of pain, intensity of fatigue, disability in mobility, intensity of anxiety, intensity of depression and the quality of life.ConclusionThe results showed that the quality of life in half of the subjects (50%) was low. There was a significant relationship between pain, fatigue, disability in mobility, anxiety and depression and the quality of life. Keywords: Quality of Life; Arthritis, Rheumatoid ; Pain; Fatigue; Anxiety; Depression